Neutrophil Extracellular Traps: A Potential Therapeutic Target in MPO-ANCA Associated Vasculitis? - O'Sullivan, Kim M.; Holdsworth, Stephen R. (Frontiers in Immunology, 2021)
Our understanding of immune recognition and response to infection and non-infectious forms of cell damage and death is rapidly increasing. The major focus is on host immunity and microbiological invasion. However, it is also clear that these same pathways are important in the initiation and maintenance of autoimmunity and the damage caused to targeted organs. Understanding the involvement of cell death in autoimmune disease is likely to help define critical pathways in the immunopathogenesis of autoimmune disease and new therapeutic targets. An important immune responder cell population in host defence and autoimmunity is the neutrophil. One autoimmune disease where neutrophils play important roles is MPO-ANCA Microscopic Vasculitis. This a severe disease that results from inflammation to small blood vessels in the kidney, the glomeruli, (high blood flow and pressure filters). One of the best studied ways in which neutrophils participate in this disease is by cell death through NETosis resulting in the discharge of proinflammatory enzymes and nuclear fragments. In host defence against infection this process helps neutralise pathogens however in auto immunity NETosis results in injury and death to the surrounding healthy tissues. The major autoimmune target in this disease is myeloperoxidase (MPO) which is found uniquely in the cytoplasm of neutrophils. Although the kidney is the major organ targeted in this disease MPO is not expressed in the kidney. Autoantibodies target surface MPO on activated circulating neutrophils resulting in their lodgement in glomerular capillaries where they NETose releasing extracellularly MPO and nuclear fragments initiating injury and planting the key autoantigen MPO. It is the cell death of neutrophils that changes the kidney from innocent bystander to major autoimmune target. Defining the immunopathogenesis of this autoimmune disease and recognising critical injurious pathways will allow therapeutic intervention to block these pathways and attenuate autoimmune injury. The insights (regarding mechanisms of injury and potential therapeutic targets) are likely to be highly relevant to many other autoimmune diseases.